MANAJEMEN KESISWAAN DALAM PENINGKATAN PELAYANAN PROSES PEMBELAJARAN DI SDN 1 PERUMNAS WAY HALIM BANDAR LAMPUNG - Apridayati (UNISAN JURNAL, 2024)
The success of an organization, including school educational institutions in a competitive environment, certainly cannot be separated from how the school's ability to find out and meet needs and provide good services, especially in the learning process effectively. Service efforts to educational users (students) are one of the important strategies for institutions to achieve quality and quality education because services to students will provide an assessment response to educational institutions. Therefore, researchers need to conduct research regarding the service of the learning process at SDN 1 Perumnas Way Halim Bandar Lampung and the efforts in it. The formulation of the research problem in general is: how to plan, organize, implement, and supervise the management of the vice principal for student affairs in improving the service of the learning process at SDN 1 Perumnas Way Halim Bandar Lampung. The method used in this research is descriptive qualitative research method. In this study, the researcher acts as a key instrument in addition to other supporting instruments such as interview guides, observation guides and audio and video recording tools. Researchers conducted research at SDN 1 Perumnas Way Halim Bandar Lampung who became the subject or source of data in this study were field teachers, student waka and madrasa heads. Data collection techniques in this study are interview and documentation techniques. The data analysis technique has four stages, namely data collection, data reduction, data presentation and finally drawing conclusions. The results of the study indicate that the planning of student management is prepared on the basis of the school's ability and meets the needs of students and the demands of the times.